Consensus of the Amapá society of implantodontics on the criteria for choosing a bone graft. - Santos Araújo , Antônio; Rauber , Silvana (Brazilian Journal of Implantology and Health Sciences, 2020)
A bone graft may be used in a variety of clinically practiced implant surgeries, namely, guided bone regeneration, extraction socket preservation or reconstruction, ridge augmentation, and sinus membrane elevation. The bone graft is of various types depending on the material, for instance, autogenous bone graft, allograft, xenograft, alloplastic graft, and autogenous bone graft with demineralized dentin matrix, which may be used alone or with other materials. Bioactive agents that promote bone formation, such as recombinant human bone morphogenetic protein-2 (rhBMP-2), have been shown to exhibit a clinically beneficial effect on bone regeneration. Here, we intend to present surgical guidelines for bone grafts and criteria for selection of bone graft materials by referring to evidence-based studies and recent lectures on the subject of ‘bone grafts for implant dentistry’ at the Amapá society of implantodontics, 2020.